Trauma-Informed School Practices Building Expertise To Transform Schools - Berardi, Anna A.; Morton, Brenda M. (Open textbook library., 2019)
This textbook represents the combined insight and experience of Morton, a k12 educator, and Berardi, a psychotherapist, both of whom are also university educators with extensive work experience serving districts and their teachers seeking to incorporate trauma-informed principles into their school culture and classroom. The authors identify that the field of education is now ready to deepen its level of response to the paradigm shift created by advances in neuroscience and traumatology. Hence, the primary focus is on identifying and applying trauma-informed educator competencies needed to transform districts, schools, educators, classrooms, and the field of education itself, while also including community members such as parents and board members in these processes - a total system makeover. At the conclusion of this text, the student, educator, or mental health professional will have a deeper understanding of what trauma-informed practice requires of them. This includes practical strategies on how to transform our learning communities in response to the devastating effect of unmitigated stress and trauma on our student's ability to learn and thrive throughout the lifespan.